Enhancing the oxidative stability of flaxseed oil using food-grade O/W Pickering emulsions stabilized by antioxidant-rich cocoa byproduct particles - Ivan Chóez-Guaranda; Yohanna Mosi-Roa; Manuel Chacón-Fuentes; Karla Garrido-Miranda; Mauricio Opazo-Navarrete; Jonathan Coronel-León; César Burgos-Díaz (Applied Food Research)
Pickering emulsions with antioxidant properties are of great interest in developing encapsulation systems for compounds that are highly susceptible to oxidation. In this study, the fabrication of antioxidant O/W Pickering emulsions using cocoa bean shell (CBS) particles with dual functionality, as both Pickering emulsifiers and interfacial reservoirs of polyphenols, for the encapsulation of flaxseed oil was demonstrated. The antioxidant-rich CBS was pretreated to obtain Pickering stabilizers, which were characterized in terms of chemical composition and antioxidant activity using gravimetry, liquid chromatography, and spectrophotometry. O/W Pickering emulsions were then prepared by microfluidization using various concentrations of CBS particles (0.5–5 % w/w) and characterized in terms of droplet size, microstructure, and physical and oxidative stability. The results showed that CBS particles contain valuable macronutrients, including proteins (18.21 %) and fibers (57.75 %), as well as flavonoids, phenolic acids, and methylxanthines, which exhibit remarkable antioxidant activity. The obtained Pickering emulsions exhibited high resistance to creaming and a reduction in droplet size as CBS particle concentration increased, which was consistent with the TURBISCAN Stability Index (TSI) data. Moreover, emulsions stabilized with ≥4.0 % (w/w) CBS particles showed high stability against creaming over 42 days of storage at room temperature. Furthermore, oxidative stability exhibited similar trends, as indicated by OXITEST values and the measurements of primary (Peroxide values) and secondary (TBARS) oxidation products over time. These findings could contribute to the development of flaxseed oil Pickering emulsions with enhanced oxidative stability and health-promoting properties for food applications.